2003
DOI: 10.1177/000348940311200202
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Laryngopharyngeal Reflux: Influence of Meals and Beverages

Abstract: Ambulatory 24-hour double-probe pH monitoring seems to be the best test to measure reflux. Artifacts caused by intake of acid foods and beverages have to be excluded, necessitating a time-consuming manual review of the 24-hour data. Dietary restrictions used to bypass these artifacts would interfere with the normal daily life situation. Therefore, the influence of food and beverages ingested during the monitoring period was studied. Data from 252 patients who underwent double-probe pH monitoring were analyzed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 13 publications
0
18
0
2
Order By: Relevance
“…An abrupt drop is frequently seen in all probes during meals. 14 Smit et al 15 found that by removing meal periods from analysis, the time of acid exposure changed from 0.3% (inclusive of meals) to 0.0% (meal periods excluded). Mathus-Vliegen et al 16 reported that excluding a 2-hour postprandial period led to an unacceptably high false-negative rate (57%).…”
Section: Resultsmentioning
confidence: 99%
“…An abrupt drop is frequently seen in all probes during meals. 14 Smit et al 15 found that by removing meal periods from analysis, the time of acid exposure changed from 0.3% (inclusive of meals) to 0.0% (meal periods excluded). Mathus-Vliegen et al 16 reported that excluding a 2-hour postprandial period led to an unacceptably high false-negative rate (57%).…”
Section: Resultsmentioning
confidence: 99%
“…However, study interpretation relies upon accurate reporting of ingestions during the study. In past studies examining acid reflux on pH monitoring, test protocol includes instructions to the patient such as “continue your typical diet,” “use the [pH] recorder's meal indicator when eating or drinking,” and “record meals in a diary” [9, 10, 14, 22]. One study that did not utilize a diary, reported that the defined meal stop/start times were “stated by the patients” [12], which would require precise recall.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that the standardization of meals or imposed dietary regimens may significantly disrupt the typical pattern of acid reflux and symptoms in patients [9, 10]. Lim et al [11] administered a questionnaire to patients with suspected gastroesophageal reflux following the completion of a 24-hour pH probe study, in which areas of food, activity, and distress were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Da auch die absoluten Zahlen im Ösophagus größer sind, hat das Aufdecken einzelner Pseudorefluxe hier einen sehr viel geringeren Einfluss auf das gesamte Messergebnis. Auch Smit [22] kommt in seiner Untersuchung zu dem Ergebnis, dass die Korrektur "per Hand" auf die Messergebnisse im Ösophagus nur einen geringen Effekt hat.…”
Section: Introductionunclassified
“…Unter Anwendung seiner eigenen Definition einer Refluxepisode unterstellen wir vier falsch positive Messergebnisse. In einer Untersuchung zu pharyngealem Reflux von Smit[22] sind 46 % der Patienten reflux-positiv. Jedoch gibt Smit die Anzahl der Patienten mit pathologischem gastropharyngealen Reflux seiner Definition entsprechend an.…”
unclassified